2000
DOI: 10.1074/jbc.275.2.1145
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Characterization of Natural Mutants of Human Aldolase B

Abstract: Fructaldolases (EC 4.1.2.13) are ancient enzymes of glycolysis that catalyze the reversible cleavage of phosphofructose esters into cognate triose (phosphates). Three vertebrate isozymes of Class I aldolase have arisen by gene duplication and display distinct activity profiles with fructose 1,6-bisphosphate and with fructose 1-phosphate. We describe the biochemical and biophysical characterization of seven natural human aldolase B variants, identified in patients suffering from hereditary fructose intolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
6
35
1
Order By: Relevance
“…Third, all three human aldolase isozymes are known to convert dihydroxyacetone phosphate and glyceraldehyde to fructose 1-phosphate (30 -32). In addition, a rabbit aldolase was shown to convert dihydroxyacetone phosphate and erythrose to sedoheptulose 1-phosphate (30), and this finding has been confirmed in this study. Furthermore, the labeling and biochemical studies showed that the rate of sedoheptulose 1-phosphate synthesis was much slower than that of fructose 1-phosphate, consistent with their cellular levels (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…Third, all three human aldolase isozymes are known to convert dihydroxyacetone phosphate and glyceraldehyde to fructose 1-phosphate (30 -32). In addition, a rabbit aldolase was shown to convert dihydroxyacetone phosphate and erythrose to sedoheptulose 1-phosphate (30), and this finding has been confirmed in this study. Furthermore, the labeling and biochemical studies showed that the rate of sedoheptulose 1-phosphate synthesis was much slower than that of fructose 1-phosphate, consistent with their cellular levels (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, to evaluate metabolic effects of the novel ALDOB variants also in actual cells, we now start cloning ALDOB cDNA in a eukaryotic expression system. Models of natural variants based on crystal structural data may also shed light on mutationinduced structural-functional alterations [Santamaria et al, 2000;Rellos et al, 2000;Esposito et al, 2002;Esposito et al, 2004a;Malay et al, 2005]. Analysis of the ALDOB three-dimensional structures clearly indicates that both Arg46 and Tyr343 are exposed to the solvent, far from the tetramer interface ( Arg 304 in the correct position for substrate binding and catalysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of various HFI-related missense mutations on ALDOB function have been investigated by in vitro expression and functional characterization of the corresponding recombinant enzymes [Brooks and Tolan, 1994;Santamaria et al, 2000;Rellos et al, 2000;Esposito et al, 2002;Esposito et al, 2004a]. Thus, to assess whether the p.R46W and p.Y343H natural ALDOB variants are associated to a functional deficiency, we expressed the corresponding recombinant enzymes in bacterial cells.…”
Section: Resultsmentioning
confidence: 99%
“…An untagged form of FBA-tb was produced because N-terminal tags have been found to affect dramatically the solubility and activity of FBA-tb produced in E. coli probably by disrupting its quaternary structure (18,49). Moreover, we found a C-terminal hexahistidinetagged form of FBA-tb to be inactive when expressed in M.…”
Section: Production Of Active Form Of Fba-tb and Evidence For Its Surmentioning
confidence: 98%